Iridium-catalyzed reductive Strecker reaction for late-stage amide and lactam cyanation - de Arriba, A; Lenci, E; Sonawane, M; Formery, O; Dixon, D (Wiley, 2017)
A new iridium-catalyzed reductive Strecker reaction for the direct and efficient formation of α-amino nitrile products from a broad range of (hetero)aromatic and aliphatic tertiary amides, and N-alkyl lactams is reported. The protocol exploits the mild and highly chemoselective reduction of the amide and lactam functionalities using IrCl(CO)[P(C6H5)3]2 (Vaska's complex) in the presence of tetramethyldisiloxane, as a reductant, to directly generate hemiaminal species able to undergo substitution by cyanide upon treatment with TMSCN (TMS=trimethylsilyl). The protocol is simple to perform, broad in scope, efficient (up to 99 % yield), and has been successfully applied to the late-stage functionalization of amide- and lactam-containing drugs, and naturally occurring alkaloids, as well as for the selective cyanation of the carbonyl carbon atom linked to the N atom of proline residues within di- and tripeptides.